Broadband Silicon-On-Insulator directional couplers using a combination of straight and curved waveguide sections - George F. R. Chen (Nature Portfolio, 2017)
Abstract Broadband Silicon-On-Insulator (SOI) directional couplers are designed based on a combination of curved and straight coupled waveguide sections. A design methodology based on the transfer matrix method (TMM) is used to determine the required coupler section lengths, radii, and waveguide cross-sections. A 50/50 power splitter with a measured bandwidth of 88 nm is designed and fabricated, with a device footprint of 20 μm × 3 μm. In addition, a balanced Mach-Zehnder interferometer is fabricated showing an extinction ratio of >16 dB over 100 nm of bandwidth.